Space enabled smart Africa (SESA) - Hugbo, Tivere (Department of Electrical Engineering, 2020)
Urbanization in Africa is growing at a rapid pace and so is the population growth. Cities in Africa are struggling to cope with the demand that urban migration brings. For example, Africa has over 60% of her population located in the urban areas. These urban locations are sprawling slums due to the massive influx of people and inadequate housing systems. The United Nations, through the Sustainable Development Goals called for a sustainable cities and communities. This project is focus on using the smart city approach to tackle these urbanization issues. With the advancement in satellite application systems, smart cities can be enabled through space technology to address these urbanization and other issues affecting the African region. Integrating space technology, such as communication, Earth observation, and satellite aided position timing & navigation application systems and small satellite technology, to the smart city paradigm could provide sustainable ways in which problems like digital division, over population, natural disaster, etc. could be managed and eradicated.